A Simple and Efficient Extraction Method for the Preconcentration of Copper in Tap Water and Linden Tea Samples Prior to FAAS Measurement - Demir, Cansu; Oner, Miray; Bodur, Suleyman; Er, Elif Ozturk; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2021)
In this study, a simple, low-cost and eco-friendly analytical method namely syringe assisted pipette tip dispersive solid phase extraction (SA-PT-DSPE) combined with slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) system was presented for the determination of copper at trace levels in linden tea and tap water samples. Under the optimal experimental conditions, limit of detection (LOD) and quantification (LOQ) values obtained for the SA-PT-DSPE-SQT-FAAS system were calculated as 3.7 and 12.5 mu g/L, respectively. The SA-PT-DSPE-SQT-FAAS system provided a 44.0-folds improvement in detection power of the conventional FAAS. The recovery results for tap water samples were calculated close to 100 % via external calibration strategy. Negative matrix effects on the analyte were observed for linden tea samples. Therefore, recovery studies were performed by matrix matching calibration strategy and percentage recoveries were found to be between 88.0-102.0 % with low standard deviation values.
Keywords: Copper; SQT-FAAS; Fe3O4 nanoparticles; Extraction; Trace analysis; LIQUID-LIQUID MICROEXTRACTION; SOLID-PHASE-EXTRACTION; COATED MAGNETIC NANOPARTICLES; SLOTTED QUARTZ TUBE; HEAVY-METALS; SPECTROMETRY; MICRO; SOLVENT; LEAD; IRON; Chemistry